Increasing Knowledge of Worm Infection in the Community at Palas Pastoran, Palas Village, Rumbai District, Pekanbaru City - Yeli Hartuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Worm infection is a disease that is still a health problem in children in developing countries, especially in children who cannot maintain personal hygiene. The aim of PkM is to increase the knowledge of the community, especially mothers who have children aged 5-12 years, to prevent helminth infections. The number of dedication participants was 15 people. The method of lecture activities and examination of feces is the Direct slide method. The results of the activity were obtained, namely filling out the mother's knowledge questionnaire about helminth infections, mothers who had less knowledge were 60%, 26.66% sufficient and 13.33% good, but after the health promotion was carried out, the results of filling out the mother's knowledge questionnaire were less than 0%, 13 was enough, 33% and good 86.66%. The results of stool examination in children with an age range of 5-12 years from 15 specimens found 4 specimens positive for STH worm eggs with Ascaris lumbricoides fertile (fertilized) worm eggs and Trichuris trichiur worm eggs, while 11 other samples were negative.